"Mga bagong b(iy) ayani ng bayan" the reception of the portrayals of TFC's Adobo Nation by selected Filipino migrants in the U.S. - De Vera, Marianne Johanna (College of Mass Communication, University of the Philippines Diliman, 2014)
"These days, the sight of overseas Filipinos, especially migrants in every region of the world, is already commonplace. Almost nine million Filipinos or 10% of the population (currently numbered at approximately 10,455,788) are located outside the country, with the figures expected to go up in the coming years (data as 2011 culled from http://www.cfo.gov.ph/pdf/statistics and Tharoor, 2010, p.23). Like Filipinos in the Philippines, this steadily growing population of Filipinos overseas face the same problems - physical, psychological and spiritual. The difference lies in the physical distance between these Filipino migrants in their second homes and their families in the Philippines who can possibly provide physical and emotional support during times of need. Given this reality, this study title "B(iy)ayani ng Bayan" studied one of ABS-CBN The Filipino Channel's (TFC) exclusive programs "adobo NATION" and its portrayals of the biggest population of Filipinos outside the Philippines (http://www.poea.gov.ph/html/statistics.html). Specifically, this thesis explored how "adobo NATION", as a product of transnationalized television (broadcast networks that purposively traverses geographical territories, utiizing satellite technology to deliver information and entertainment content [Thomas, 2006, p.244], portrayed overseas Filipinos. This study focused on TFC given the program's high viewership and production values (TFC Internet Protoco; Television [IPTV] Hits as of 2012), and the author's connections as an employee of ABS-CBN Global (mother company of ABS-CBN TFC). Using multi-methods (content analysis, focus and email interviews), this research revealed what representations of Filipino migrants "adobo NATION" has presented; what trends these portrayals have formed, how cloes they were to real-life situations; and how Filipinos overseas perceived these representtions within the program. Results of the study showed that some Filipino migrants are seen and portrayed as economic successes and sources of financial support or "bayani" and "biyaya (blessings) ng bayan". However, majority of the informants say that "adobo NATION's" dominant portrayals are of overseas Filipinos as achievers who bring prode to the entire Filipino community, consistent with the thesis' over-all concept of Filipinos as blessings."